Flutuação anual e interanual da riqueza de espécies de desmídias (Chlorophyta – Conjugatophyceae) em um lago de inundação amazônico de águas pretas (Lago Cutiuaú, Estado do Amazonas, Brasil) = Annual and interannual fluctuation of desmids species in a black water Amazon floodplain lake (Lago Cutiuaú, Amazonas State, Brazil) - Sergio Melo; Karla Ferreira de Souza (Acta Scientiarum: Biological Sciences, 2009)
Nesta pesquisa foi avaliada a flutuação sazonal e interanual da riqueza específica de desmídias ao longo de diferentes períodos do ciclo hidrológico de 2002 a 2004, em um lago de inundação de águas pretas da bacia do rio Negro, no Estado do Amazonas. O lago estudadoapresentou marcada flutuação anual na profundidade da coluna d’água e elevados valores de temperatura ao longo de todo o estudo, enquanto os valores de pH e condutividade elétrica foram baixos. Foram identificadas 105 espécies de desmídias distribuídas nas famíliasClosteriaceae, Gonatozygaceae e Desmidiaceae. Destas, 23 constituem primeira citação para o Estado do Amazonas e se encontram ilustradas no presente estudo. O período de enchente foi o que apresentou maior riqueza de espécies, em oposição aos demais períodos, que apresentaramvalores similares. Em escala interanual, o ano de 2003 foi caracterizado por apresentar maior número de táxons. Os gêneros Staurastrum Meyen e Closterium Nitzch foram os que apresentaram maior número de espécies durante o estudo. A maioria das espécies registradas esteve presente em menos de 10% ou entre 10 e 30% das amostras analisadas, sendo consideradas raras ou esporádicas, respectivamente. In this study, the seasonal and interannual fluctuations of desmids species richness was investigated for three years in an Amazon black water floodplain lake in the Negro River basin, Amazon State. The studied environment showed a great annual fluctuation of water column depth and high temperature values with little seasonal fluctuations. In general, pH and electrical conductivity values were low. One hundred five desmids species were identified distributed among families Closteriaceae, Gonatozygaceae and Desmidiaceae. Twenty three species are new references to Amazon State and are illustrated in this study. A marked seasonal fluctuation of desmids species was registered in association with the inundation pulse. The increased water level was the period of more species richness; on the other hand, the others periods showed low and similar species number. An interannual fluctuation of desmids species number was also registered, with the highest number in 2003, especially in the increased water level. Staurastrum Meyen and Closterium Nitzch were the genera with the highest species numbers. Based on this occurrence, the majority of species registered was rare or sporadic, registered in less than 10% or between 10 and 30% of total analyzed sample, respectively.